Analisis Peran Guru dalam Pembentukan Karakter Siswa Kelas V di SDN Bagik Krongkong - Sarudin Efendi; Laelatun Rohaniah; Nelsi Putri; Ulin Nuha (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2024)
Character has a meaning like universal human nature where it adheres to the life factors of each individual. Character is like spiritual nature, morals or manners, motivation, and skills. This research focuses on the role of teachers in forming the character of class student V at SDN Bagik Krongkong. It aims to analyze the role of teachers in forming the character of class V students, as well as the inhibiting factors and supporting factors in forming the character of class V students at SDN Bagik Krongkong. The teacher's role, which is the research's focus, is as an educator, demonstrator, class manager, motivator, and evaluator. The character values that are the focus of the research are religion, honesty, discipline, independence, social caring, and responsibility. This research uses a qualitative method with a descriptive approach. The data collection techniques used were observation, interviews, and documentation with research subjects consisting of fifth-grade teachers and students. The data analysis stages are data collection, reduction, presentation, and conclusion. Testing the validity of the data in this study used triangulation techniques. The results of the research show that: (1) The role of teachers in forming the character of class V students at SDN Bagik Krongkong is carried out with several teacher roles, namely teacher as educator, teacher as demonstrator, teacher as class manager, teacher as motivator and teacher as evaluator, (2) Supporting factors for the role of teachers in forming the character of class V students at SDN Bagik Krongkong are the family environment and facilities and infrastructure, while factors inhibiting the role of teachers in forming the character of class V students at SDN Bagik Krongkong include the family environment and teachers.